Past 12-month and lifetime comorbidity and poly-drug use of ecstasy users among young adults in the United States: Results from the National Epidemiologic Survey on Alcohol and Related Conditions - Keyes, Katherine M. (2008)
BACKGROUND: Ecstasy use is prevalent among young people and often co-occurs with other drug use, but little is known about the past 12-month and lifetime psychiatric comorbidity and specific additional drug abuse among young adult ecstasy users in the general population. To provide this information, we compared current ecstasy users to former users, other illicit drug users, and non-illicit drug users. METHOD: Data were gathered in a face-to-face survey of the United States conducted in the 2001–2002 (NESARC). Participants were household and group quarters residents aged 18–29 years (n = 8666). We measured current ecstasy use defined as any use in the past year; former ecstasy use as use prior to the past year only; other lifetime drug use included any drug other than ecstasy; lifetime non-illicit drug use as no illicit drug use. Associations were determined for nine other classes of illicit drugs, eight personality disorders, and seven mood and anxiety disorders. RESULTS: Of current ecstasy users, 44% used >3 other classes of illicit drugs in the past year, compared to 1.6% of non-ecstasy drug users. Current ecstasy use was associated with current anxiety (OR = 3.7), specifically panic disorder (OR = 7.7) and specific phobia (OR = 4.1), also alcohol abuse (OR = 21.6) and dependence (OR = 4.1) and any personality disorder (OR = 5.1) compared to non-illicit drug users. CONCLUSIONS: Results indicate important differences in comorbidities of current and former ecstasy users compared to other drug users and lifetime non-illicit drug users that may affect phenotype definitions and etiologic studies. Ecstasy use may represent a distinct population of drug users for which unique treatments may be necessary.